2020
DOI: 10.3847/1538-4357/ab64f4
|View full text |Cite
|
Sign up to set email alerts
|

A Noncorotating Gas Component in an Extreme Starburst at z = 4.3

Abstract: We report the detection of a non-corotating gas component in a bright unlensed submillimeter galaxy at z = 4.3, COSMOS-AzTEC-1, hosting a compact starburst. ALMA 0.17 and 0.09 arcsec resolution observations of [C ii] emission clearly demonstrate that the gas kinematics is characterized by an ordered rotation. After subtracting the best-fit model of a rotating disk, we kinematically identify two residual components in the channel maps. Both observing simulations and analysis of dirty images confirm that these t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 73 publications
3
18
0
Order By: Relevance
“…The sample of SMGs and their proposed cQGs descendants at z ∼ 2 are located in distinct regions of the diagram, but the separation is what is expected given that the SMGs will grow in stellar mass in their current starburst episode and in size due to the observed minor mergers, bringing the location of the populations into agreement and furthering the strength of their evolutionary connection. This evolutionary sequence is also strengthened by recent analysis showing evidence for gaseous rotationally-support disks in some of the SMGs in the sample (e.g., Jones et al 2017;Tadaki et al 2020) and other results on z ∼ 2 cQGs exhibiting rotationally-supported stellar disks (Newman et al 2015;Toft et al 2017).…”
Section: Connecting Submillimeter and Quiescent Galaxiessupporting
confidence: 73%
“…The sample of SMGs and their proposed cQGs descendants at z ∼ 2 are located in distinct regions of the diagram, but the separation is what is expected given that the SMGs will grow in stellar mass in their current starburst episode and in size due to the observed minor mergers, bringing the location of the populations into agreement and furthering the strength of their evolutionary connection. This evolutionary sequence is also strengthened by recent analysis showing evidence for gaseous rotationally-support disks in some of the SMGs in the sample (e.g., Jones et al 2017;Tadaki et al 2020) and other results on z ∼ 2 cQGs exhibiting rotationally-supported stellar disks (Newman et al 2015;Toft et al 2017).…”
Section: Connecting Submillimeter and Quiescent Galaxiessupporting
confidence: 73%
“…The significant lower velocity dispersion observed in this component imply that F07599NE may have a different origin from F07599S. Similar gas substructure has been observed in high-z starbursts in [C ii] emission but with a much smaller physical separation (∼ 2 kpc; Tadaki et al 2020), where the formation of subcomponent is expected to be associated with a gravitationally unstable disk or shocks. By contrast, the large physical separation (projected distance of ∼ 19 kpc) observed between F07599NE and the galaxy nucleus indicates that the CO plume feature observed in the NE direction could be a separate component, likely associated with the tidal debris reminiscent of a previous merger.…”
Section: Origin Of the Off-center Co Componentssupporting
confidence: 53%
“…A vast sample of rotating galaxies has been well studied at < 4 (e.g., Epinat et al 2008;Förster Schreiber et al 2009;Gnerucci et al 2011), revealing dynamical masses and empirical scaling relations. While a number of clumpy or merging galaxies have been detected at > 4 (e.g., Carniani et al 2018;Pavesi et al 2018;Díaz-Santos et al 2018), and a handful of rotating starburst or quasar host galaxies at ∼ 4 − 6 have been well-modelled (e.g., Jones et al 2017;Pensabene et al 2020;Tadaki et al 2020;Fraternali et al 2021;Lelli et al 2021), only two unlensed rotating main sequence galaxies have been observed at ∼ 4 − 6: HZ9 (Capak et al 2015) and J0817 (Neeleman et al 2017(Neeleman et al , 2020 5 . In this section, we add six new ∼ 4 − 6 rotators from the ALPINE sample to this class: CG32, DC396844, DC494057, DC552206, DC881725, and VC.7875.…”
Section: Main Sequence Rotators At Z>4mentioning
confidence: 99%